Analysis Risk Based Inspection API 581 on LPG Spherical Tank at PT. XYZ - Trahmawan, Sigit; Siradj, Eddy Sumarno; Fatriansyah, Jaka Fajar (UI Scholars Hub, 2024)
Liquified petroleum gas (LPG) spherical tanks are pressure vessel equipment for storing fuel gas products. The high pressure along with the fuel gas inside as flammable and combustible substance means that this equipment might result major accident hazard such as explosion, fires and environmental pollution. This study is aimed calculated and mitigate risk on 500 metric ton capacity LPG spherical tank using Risk-based inspection (RBI) analysis method that makes risk as its foundation. This RBI method uses quantitative analysis referring to API 581 to determine the risk of LPG Spherical Tank by determining the probability of failure (PoF) and the consequences of failure (CoF). From the results of the risk assessment will be determined appropriate methods and scheduling inspection for LPG spherical tank. As result, thinning defect mechanism is one that influences the possibility of failure of LPG ball tank equipment with a failure rate of 4.13 E-06 failure/year. The result risk assessment of LPG ball tank is at the medium-high risk level with the probability of failure being in category 1 (low) and the consequence of failure being in category E (high). Meanwhile, the recommended inspection method for LPG tank is internal and external inspection in the form of visual examination and ultrasonic thickness measurement with an inspection interval every 5 (five) years.